2013
DOI: 10.1007/978-3-642-39218-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Phishing and Organisational Learning

Abstract: The importance of addressing the human aspect in information security has grown over the past few years. One of the most frequent techniques used to obtain private or confidential information from humans is phishing. One way to combat these phishing scams is to have proper security awareness programs in place. In order to enhance the awareness and educational value of information security awareness programs, it is suggested that an organisational learning model, characterised by so called single-loop and doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Lab Student [61], [204], [211]- [218] [153], [219]- [225], [226] a , [227] a [228]- [233], [234] a Employee [235] a Unrestricted [203], [236], [237] a [238], [239], [240] a , [241] a [242], [243], [244] a Real Student [245] [202], [246], [247] [201], [248]-[251] Employee [252] [253]- [255] [10], [256], [257] Unrestricted [217], [258]- [260] [213], [261]- [266] a Studies that only asked participants about their vulnerability (Q/A) instead of showing them the email/website [220], [221], [228], [246], [251], [259] [10], [201], [223], [231], [248], [255], [257] 3 [202],…”
Section: Selected User Study Literaturementioning
confidence: 99%
“…Lab Student [61], [204], [211]- [218] [153], [219]- [225], [226] a , [227] a [228]- [233], [234] a Employee [235] a Unrestricted [203], [236], [237] a [238], [239], [240] a , [241] a [242], [243], [244] a Real Student [245] [202], [246], [247] [201], [248]-[251] Employee [252] [253]- [255] [10], [256], [257] Unrestricted [217], [258]- [260] [213], [261]- [266] a Studies that only asked participants about their vulnerability (Q/A) instead of showing them the email/website [220], [221], [228], [246], [251], [259] [10], [201], [223], [231], [248], [255], [257] 3 [202],…”
Section: Selected User Study Literaturementioning
confidence: 99%
“…Vulnerabilities References ` Financial benefit/ desire for monetary gain (Aggarwal, Kumar, & Sudarsan, 2014;Bere et al, 2015;Sahu & Dubey, 2014;Vayansky & Kumar, 2018;Zhou, Zhang, Xiao, Wang, & Lin, W. 2014;Oliveira et al, 2017) Curiosity (Aggarwal, Kumar, & Sudarsan, 2014;Bere et al, 2015;Cho, Cam, & Oltramari, 2016;Fette, Sadeh, Tomasic, 2007;Wash & Cooper, 2018;O'Kane, Sezer, & Carlin, 2018) Carelessness (Aburrous et al, 2010;Bere et al, 2015;Chiew, Chang, & Tiong, 2015;Kearney & Kruger, 2013;Laszka, Lou, & Vorobeychik, 2016;Miyamoto, Hazeyama, & Kadobayashi, 2005;Nagalingam, Narayana Samy, Ahmad, Maarop, & Ibrahim, R. 2015;Parmar, 2012;Workman, 2008;Wright & Marett, 2010;Zhang, Ren, & Jiang, 2016;Zhou et al, 2014) Trust in the sender (Alseadoon, Othman, Foo, & Chan, 2013;Bere et al, 2015;Cho, Cam, & Oltramari, 2016;Harrison, Vishwanath, & Rao, 2016;Huang, Tan, & Liu, 2009;Ivaturi, & Janczewski, 2012;Komatsu, Takagi, & Takemura, 2013;Patel & Luo, 2007;Romanov, Semenov, Mazhelis, & Veijalainen, J. 2017;Vayansky & Kumar, 2018) Lack of awareness; ignorance (Bann, Singh, & Samsudin, 2015;Caputo et ...…”
Section: Constructsmentioning
confidence: 99%
“…In an effort to demonstrate (not to prove) the possible presence of homeostatic principles in information security behaviour, the ensuing paragraphs of this section refer to case studies that were conducted earlier and that have already been reported in the literature (Kearney and Kruger, 2013, 2014). The case studies entail practical information security exercises that were conducted at a very large utility company with over 3,500 information technology users.…”
Section: The Theory Of Risk Homeostasismentioning
confidence: 99%
“…The results were unexpected and contradictory to the high levels of security awareness; of the 280 users who responded over a short period of time, 231 (83 per cent) revealed the required personal details. Complete details of the phishing exercise were reported in Kearney and Kruger (2013). This test was later on followed up with a similar phishing test, and results showed that there was no improvement in terms of the number of people who gave away their personal details; in fact, the numbers increased from the first to the second test.…”
Section: The Theory Of Risk Homeostasismentioning
confidence: 99%
See 1 more Smart Citation